Structure of cartoons, narrative skills and perception of values/countervalues in primary school / Estructura de los dibujos animados, habilidades narrativas y percepción de valores/contravalores en Educación Primaria. Issue 3 (3rd July 2019) - Oregui, Eider; Aierbe, Ana
Abstract: This study analyses whether narrative skill and the perception of values/countervalues among students in primary school vary according to the structure (narrative vs non-narrative) of the episodes of fiction viewed, the grade age (third and sixth, 8–12 years old), sex and attentional level. With this purpose in mind, quantitative and qualitative methodologies were implemented. The most noteworthy results include the higher narrative skill and perception of values/countervalues of students in the sixth grade of primary school and those who viewed an episode with a narrative structure. The conclusion is that when addressing narrative skills and the education in values/countervalues from the formal and informal spheres, special importance should be attached to the structure of the fiction contents, given that it can to some extent help students make the messages meaningful in terms of values and countervalues.